2012
DOI: 10.1520/acem-2012-0004
|View full text |Cite
|
Sign up to set email alerts
|

Variability Analysis of the Bulk Resistivity Measured Using Concrete Cylinders

Abstract: Prepared in cooperation with the Indiana Department of Transportation and Federal Highway Administration. Abstract. Many agencies are interested in using a rapid test method for measuring the electrical properties of concrete (i.e., the resistivity or conductivity) since the electrical properties can be related to fluid transport (e.g., ion diffusion). The advantage of electrical testing is that it is relatively easy to perform and the test method is relatively fast (less than a minute). Over the last century,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 28 publications
4
27
0
Order By: Relevance
“…It is also observed from Table 4 that theoretical geometric correction factor (2.63) closely matches with average ratios at 28, 56, 91 and 161 days for all cementitious mixtures. Recent study conducted by Spragg et al (2012) also showed similar trend of results for comparison of surface and bulk resistivity at different ages. This relationship of ratio between surface and bulk resistivity actually represents an adjustment factor due to geometric size difference for measurement of electrical resistivity on different sizes of specimens.…”
Section: Measurement Of Bulk Electrical Resistivitysupporting
confidence: 74%
See 1 more Smart Citation
“…It is also observed from Table 4 that theoretical geometric correction factor (2.63) closely matches with average ratios at 28, 56, 91 and 161 days for all cementitious mixtures. Recent study conducted by Spragg et al (2012) also showed similar trend of results for comparison of surface and bulk resistivity at different ages. This relationship of ratio between surface and bulk resistivity actually represents an adjustment factor due to geometric size difference for measurement of electrical resistivity on different sizes of specimens.…”
Section: Measurement Of Bulk Electrical Resistivitysupporting
confidence: 74%
“…This test can be performed by utilizing conductive medium and needs to be remembered that surface finish needs to be flat as much as possible for proper contact pressure and sponges were used between sample and plates to obtain better contact. Recently, Spragg et al (2012) analyzed variability studies on 12 different cementitious mixtures for BR and SR and correlation was established at testing ages of 28, 56 and 91 days. Additionally, the effect of electrode resistance was discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In this test, we adopted end to end AC two point test and referred to the setup of Spragg et al (2011), as shown in Fig. 2(a).…”
Section: Test Methodsmentioning
confidence: 99%
“…Resistance of mortar was calculated based on the method applied by Spragg et al (2011). Since high external pressure was used in this test, there is not much difference between top and bottom sponge resistance and…”
Section: Methods Of Calculating the Electrical Conductivitymentioning
confidence: 99%
See 1 more Smart Citation